Novel Analytical Methods in Food Analysis - Delahaut, Philippe; Marega, Riccardo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint provides information on the novel analytical methods used to address challenges occurring at academic, regulatory, and commercial level. All topics covered include information on the basic principles, procedures, advantages, limitations, and applications. Integration of biological reagents, (nano)materials, technologies, and physical principles (spectroscopy and spectrometry) are discussed. This reprint is ideal for professionals of the food industry, regulatory bodies, as well as researchers.